The enigma of primary hypertension in childhood - Falkner, Bonita (Frontiers in Cardiovascular Medicine, 2022)
Beginning in the 1970s hypertension in children and adolescents has been defined as systolic and/or diastolic blood pressure (BP) that is equal to or greater than the 95th percentile of the normal distribution of BP in healthy children. The definition of hypertension in adults is based on longitudinal data that defines the risk for subsequent adverse outcomes related to hypertension including heart failure, kidney failure, stroke, or death. The statistical definition of hypertension continues to be is used because data there are no data that link a BP level in childhood with heightened risk for these adverse outcomes in adulthood. Findings from clinical and epidemiologic research has advanced understanding of high BP in childhood. These findings have led to some variations in definitions of high BP in childhood. While hypertension in some children can be secondary to underlying kidney, cardiovascular, or endocrine disorder, it is now known that primary (essential) hypertension can be present in childhood. The prevalence of hypertension in childhood is approximately 2-5 percent and another 13-18 percent of children and adolescents are at heightened risk for developing hypertension; and the leading cause of hypertension is primary hypertension, especially in adolescents. For children and adolescents with secondary hypertension, the treatment can focus on managing the underlying cause of hypertension. Less is known about managing primary hypertension in childhood, including diagnosis, evaluation, treatment, and possibilities for prevention. The phenotype of primary hypertension in childhood, and recent findings will be discussed